Determination of Urinary 1‐Hydroxypyrene for Biomonitoring of Human Exposure to Polycyclic Aromatic Hydrocarbons Carcinogens by a Lanthanide‐functionalized Metal‐Organic Framework Sensor. (27th December 2016) - Hao, Ji‐Na; Yan, Bing
Abstract : 1‐Hydroxypyrene (1‐HP), which is a biomarker of polycyclic aromatic hydrocarbons (PAHs) carcinogens and represents the internal dose of PAHs exposure in the human body, is detected by a newly designed luminescent Eu‐functionalized metal‐organic framework (1a ) sensor. The luminescence of1a can be effectively quenched by 1‐HP via a fluorescent resonant energy transfer process, thus achieving its recognition of 1‐HP. This is the first use of lanthanide metal‐organic frameworks (Ln‐MOFs) as chemical sensors for 1‐HP. The probe exhibits outstanding performances for sensing 1‐HP, such as high selectivity, excellent sensitivity, fast response, and good reusability. Importantly, the sensing system enables the detection of 1‐HP in real human urine specimens, and a portable 1‐HP urine test paper is also developed. Hence, the reported 1‐HP sensing platform has promising application potential for clinical diagnosis of the intoxication level of PAHs. Abstract : A novel europium‐functionalized metal‐organic framework is constructed that can act as the first example of a fluorescent sensor for urinary 1‐hydroxypyrene, which is the metabolite and biomarker of human exposure to polycyclic aromatic hydrocarbons carcinogens.